2021
DOI: 10.1177/1533033820985866
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparison of Helical Tomotherapy, Volumetric-Modulated Arc Therapy, and Intensity-Modulated Proton Therapy for Angiosarcoma of the Scalp

Abstract: Objective: We compared radiotherapy plans among helical tomotherapy (HT), volumetric-modulated arc therapy (VMAT), and intensity-modulated proton therapy (IMPT) for angiosarcoma of the scalp (AS). Methods: We conducted a planning study for 19 patients with AS. The clinical target volume (CTV) 1 and CTV2 were defined as the gross tumor volume with a specific margin and total scalp, respectively. For HT and VMAT, the planning target volume (PTV) 1 and PTV2 were defined as CTV1 and CTV2 with 0.5-cm margins, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
8
1
Order By: Relevance
“…Previous studies suggested that total scalp irradiation was a more effective treatment than local irradiation [37,39,40]. Mizuno et al [41] compared PTV coverage and doses to OAR among helical tomotherapy, volumetric-modulated arc therapy, and intensity-modulated proton therapy (IMPT) and showed that all three techniques achieved sufficient coverage and satisfactory homogeneity for PTV. The present study appears to be the first to examine the clinical efficacy of IMRT for ASF patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that total scalp irradiation was a more effective treatment than local irradiation [37,39,40]. Mizuno et al [41] compared PTV coverage and doses to OAR among helical tomotherapy, volumetric-modulated arc therapy, and intensity-modulated proton therapy (IMPT) and showed that all three techniques achieved sufficient coverage and satisfactory homogeneity for PTV. The present study appears to be the first to examine the clinical efficacy of IMRT for ASF patients.…”
Section: Discussionmentioning
confidence: 99%
“…HT could provide higher dose homogeneity, consistent with other literature reports. [8][9][10] For pediatric patients during cranial irradiation, the hippocampus should be avoided from irradiation as much as possible. The hippocampal injury in cranial irradiation could result in potential cognitive decline, especially in terms of short-term memory formation and recall.…”
Section: Discussionmentioning
confidence: 99%
“…Many different radiation modalities and techniques have been performed for dosimetric discussion for the tumor involving the scalp or calvarium. [5][6][7][8][9][10][11] IMRT could provide the best target-dose homogeneity and coverage among 3DCRT and HDR techniques in extensive scalp lesion irradiation. 5 RapidArc (RA) was selected as the optimal solution, with marginally better conformality, shorter delivery time, and lower monitor units than static IMRT for total dura irradiation.…”
Section: Introductionmentioning
confidence: 99%
“… 19 The definition of CI was previously described in detail. 16 Differences of dosimetric parameters between the two techniques were analyzed by Student's t-test. Statistical analyses were carried out with EZR, 20 a graphical user interface for R Version 3.4.1 (The R Foundation for Statistical Computing, Vienna, Austria).…”
Section: Methodsmentioning
confidence: 99%
“… 14 , 15 In recent years, proton therapy has gradually spread and intensity-modulated proton therapy (IMPT) enables an excellent dose distribution. 16 Our hypothesis was that IMPT could achieve comparable target coverage and hippocampus- and scalp-avoidance compared with IMRT. To investigate this hypothesis, HA-WBRT plans using HT and IMPT were generated and a planning study comparing dosimetric data of the two techniques was conducted.…”
Section: Introductionmentioning
confidence: 99%